Fluorescent organic nanoparticles (FONs) for selective recognition of Al3+: application to bio-imaging for bacterial sample. Issue 44 (18th April 2016) - Huerta-Aguilar, Carlos Alberto; Raj, Pushap; Thangarasu, Pandiyan; Singh, Narinder
Abstract : (a) Changes in fluorescence upon successive addition of Al 3+ ions to salpn-ONPs; (b) titration profile of fluorescence; (c) recognition of Al 3+ through bio-fluorescence Staphylococcus aureus bacterial cells. Abstract : The development of a novel chemo-sensor for the detection of Al 3+ with high sensitivity in aqueous solution is widely considered an important research goal because of the importance of such probes in medicine, living systems and the environment. In this work, we describe a new fluorescent probe, a Schiff's base N, N ′-propylenebis(salicylimine) (salpn) as fluorescent organic nanoparticles for Al 3+ . The study shows that salpn detects Al 3+ with the detection limit as low as 1.24 × 10 −3 mM, indicating that the chemo-sensor has high sensitivity in aqueous medium, and the fluorescence intensity increases with the increasing Al 3+ concentration in the presence of the salpn-ONPs which act as chemo-sensors. The interference of common coexistent metal ions such as Mn 2+, Mg 2+, Co 2+, Fe 3+, Ni 2+, Zn 2+, Sr 2+, Ag +, Sm 3+, Al 3+, Cd 2+, Ba 2+, Na + and K + was tested, showing that salpn-ONPs efficiently detect Al 3+ ions with small interference from Cu 2+ and Cr 3+ . Finally, the efficiency of salpn to as a fluorescent probe for Al ion in living systems was evaluated in Gram-negative and Gram positive bacteria, and con-focal laser scanning microscopy confirms its utility that this chemo-sensor efficiently detects Al 3+ ion in Staphylococcus aureus enclosed by a single membrane.